3D Printing in Medicine - Rybicki, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
3D Printing in Medicine publishes 3D printing innovation that impact medicine. Authors can communicate and share Standard Tessellation Language (STL) and related files via the journal. In addition to publishing techniques and trials that will advance medicine with 3D printing, the journal covers "how to" papers to provide a forum for translating applied imaging science.
Keywords: Radiology; Surgery; Biomedical engineering; Biomaterials; Imaging / Radiology; Surgery; Biomedical Engineering and Bioengineering; Biomaterials